Dental and oral manifestations in a patient with hypophosphatasia: a case report - Alshareef, Saba M.; Alwakeel, Abdulaziz A.; Alshehri, Faisal S.; Arakkalvettath, Mohamed R.; Ali, Mahmoud A. Mustafa (International Journal of Contemporary Pediatrics, 2026)
Hypophosphatasia (HPP) is an uncommon inherited metabolic disorder caused by deficient activity of tissue‑nonspecific alkaline phosphatase (TNAP), resulting in impaired mineralization of skeletal and dental tissues. Dental manifestations are often among the earliest clinical signs and may include premature tooth loss, enamel and dentin defects, and delayed eruption. A 13‑year‑old female with a confirmed diagnosis of infantile‑onset congenital HPP presented with pain in the upper left posterior region. She was receiving enzyme replacement therapy with asfotase alfa along with growth hormone supplementation. Clinical and radiographic examination revealed a non‑vital maxillary first molar with a defective restoration, generalized enamel and dentin defects, periodontal involvement, mobility of anterior teeth, delayed and ectopic eruption, and malocclusion characterized by an anterior open bite with midline deviation. Endodontic management followed by definitive restoration of the affected tooth successfully resolved the patient’s symptoms. A comprehensive dental care plan including oral hygiene reinforcement, caries control, and extraction of non‑restorable teeth was instituted, with long‑term follow‑up planned. This report highlights the importance of early diagnosis and coordinated multidisciplinary dental care in patients with HPP.